RIGHTS AS TRUMPS AND BALANCING: RECONCILING THE RRECONCILABLE? - João Costa Neto (Revista Direito GV)
There appears to be a widespread assumption among those who defend balancing in constitutional rights that it is incompatible with the idea of rights as trumps, because public interests and constitutional rights are to be balanced without any type of pre-fixed priority or lexical ordering. My purpose in this article is to show that both trumping and balancing are not only compatible, but possibly complementary. What i will argue is that it is not only possible to have a workable arrangement of constitutional rights that incorporates both trumping and balancing, but it is also better and more plausible if we have one.